The different pathways of HIV genomic RNA translation. (24th November 2010) - Chamond, Nathalie; Locker, Nicolas; Sargueil, Bruno
Abstract : Lentiviruses, the prototype of which is HIV-1, can initiate translation either by the classical cap-dependent mechanism or by internal recruitment of the ribosome through RNA domains called IRESs (internal ribosome entry sites). Depending on the virus considered, the mechanism of IRES-dependent translation differs widely. It can occur by direct binding of the 40S subunit to the mRNA, necessitating a subset or most of the canonical initiation factors and/or ITAF (IRES trans -acting factors). Nonetheless, a common feature of IRESs is that ribosomal recruitment relies, at least in part, on IRES structural determinants. Lentiviral genomic RNAs present an additional level of complexity, as, in addition to the 5′-UTR (untranslated region) IRES, the presence of a new type of IRES, embedded within Gag coding region was described recently. This IRES, conserved in all three lentiviruses examined, presents conserved structural motifs that are crucial for its activity, thus reinforcing the link between RNA structure and function. However, there are still important gaps in our understanding of the molecular mechanism underlying IRES-dependent translation initiation of HIV, including the determination of the initiation factors required, the dynamics of initiation complex assembly and the dynamics of the RNA structure during initiation complex formation. Finally, the ability of HIV genomic RNA to initiate translation through different pathways questions the possible mechanisms of regulation and their correlation to the viral paradigm, i.e. translation versus encapsidation of its genomic RNA.